Pengaruh Kebijakan Hutang, Likuiditas dan Profitabilitas Terhadap Kebijakan Dividen: Studi pada Perusahaan Farmasi yang Terdaftar di BEI Tahun 2017-2020 - D A Wulandari (Studi Ekonomi dan Kebijakan Publik, 2023)
Purpose: The study is to determine the impact of debt policy on the IDX listed pharma dividend policy, liquidity impact on the IDX listed pharma dividend policy, and profitability impact on the IDX listed pharma dividend policy. The impact of debt policy, liquidity and profitability on the dividend policy of pharmaceutical companies concurrently or partially listed on the IDX. Methodology: This study uses quantitative methods and secondary data. The scope of this research relates to data on manufacturing companies listed on the Indonesia Stock Exchange in 2017 - 2020. Results: Results: The results of multiple linear regression analysis show that debt, liquidity, and profitability policies have an effect on dividend policy on the Indonesia Stock Exchange. On the other hand, some profitability has a negative effect on dividend policy. However, debt and liquidity policies have a partial positive effect on dividend policy. Limitations: Only tested 3 factor variables that affect dividen policy in a certain period. Contribution: It is hoped that this research can be useful for investors who will invest in certain pharmaceutical business sectors to be more careful in paying attention to various factors that affect stock returns.